Análise espacial dos indicadores epidemiológicos de hanseníase e de serviços da atenção primária à saúde bucal do Norte e Nordeste do brasil, 2012 a 2021 - Morais, Cirliane de Araújo (2023)
Leprosy is a neglected tropical disease caused by the bacillus Mycobacterium leprae. Thus, this research aims to analyze the epidemiological indicators of leprosy and primary oral health care services in the North and Northeast of Brazil, from 2012 to 2021. This is a quantitative epidemiological observational study of the ecological type, carried out with data from the municipalities of the North and Northeast .The dependent variable was the detection coefficient of new leprosy cases with data obtained from SINAN and DATASUS portal. The independent variables were social determinants from the 2010 IBGE Demographic Census and indicators of oral health care in Primary Care, collected from the Primary Care e-Manager. A descriptive spatial analysis was performed using the GeoDa 0.9.9.10 software, and regression analysis was performed using the Jamovi software version 2.3.21. All thematic maps were prepared with QGIS software version 3.28.3. The results show a heterogeneous spatial distribution of leprosy in the regions analyzed, with four hyperendemic states, based on the overall detection coefficient of new cases, namely Maranhão (58.56/100,000 inhabitants), Pará (41.25/100,000 inhabitants), Tocantins (93.73/100,000 inhabitants) and Rondônia (40.21/100,000 inhabitants). Regarding the occurrence of clusters, the Northeast presented more high-high spatial clusters, with a total of 43 sites and only 11 in the North, with statistical significance ranging from p=0.05, p=0.01 and p =0.001. In the regression analysis in relation to the sociodemographic variables, in the North there were five significant variables, p<0.05, namely: % of the population living in households with toilets and piped water, municipal human development index (HDI), % of 25 years or older with complete higher education, % of employed persons aged 18 and over who are self-employed, and maximum per capita household income of the poorest 10 quintiles, while in the Northeast there were only three: % of employed persons aged 18 and over who are self-employed, % of the population in households with piped water and % of persons in households with walls other than masonry or wood fittings. Regarding oral health indicators, only one indicator per region was significant: in the North it was the percentage of coverage of oral health teams per municipality and in the Northeast, it was the number of oral health teams per municipality. It can be concluded that leprosy is still endemic in the North and Northeast regions, and it is necessary to expand and facilitate access to health services.